The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/15421406.2015.1044361
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separations in Mixtures of a Flexible Polymer and a Cholesteric Liquid Crystal in the Presence of an External Field

Abstract: We present a mean field theory to describe phase behaviors in mixtures of a flexible polymer and a cholesteric liquid crystal under an external magnetic or electric field. Taking into account a chiral coupling between liquid crystals under the external field, we examine twist-untwist phase transitions and phase separations in the mixtures. Depending on the strength of the external field, we predict cholesteric-paranematic (Ch + N), nematic-paranematic (N + pN), cholesteric-nematic (Ch + N) phase separations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…5 and 6. 45 Field-induced cholesteric-nematic phase transitions have been observed in a mixtures of cholesterol chloride, nonanoate, and oleyl carbonate at a field of 3-5× 10 5 V/m. 5 It has been shown that CNT temperature decreases with increasing the applied field and a nematic phase appears for wide temperature ranges.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6. 45 Field-induced cholesteric-nematic phase transitions have been observed in a mixtures of cholesterol chloride, nonanoate, and oleyl carbonate at a field of 3-5× 10 5 V/m. 5 It has been shown that CNT temperature decreases with increasing the applied field and a nematic phase appears for wide temperature ranges.…”
Section: Discussionmentioning
confidence: 99%